A cross-sectional mental-health survey of Chinese postgraduate students majoring in stomatology post COVID-19 restrictions - Zhang, Yuwei; Jia, Yue; MuLaTiHaJi, MaErWa; Mi, Yiying; Mei, Yukun; Sun, Tianxiang; Shi, Haibo; Zhang, Yifei; Zhang, Yikun; Zou, Rui; Niu, Lin; Dong, Shaojie (Frontiers in Public Health, 2024)
Background The psychological status of Chinese postgraduate students majoring in stomatology after the COVID-19 restrictions still remains unclear. The objective of this study is to evaluate the mental status through a cross-sectional survey and gather related theoretical evidence for psychological intervention on postgraduate students majoring in stomatology. Methods An online survey was administered, and subjective well-being, anxiety, stress and depression symptoms were assessed using the 5-item World Health Organization Well-Being Index (WHO-5), item Generalized Anxiety Disorder Scale (GAD-7), 10-item Perceived Stress Scale (PSS-10), and Patient Health Questionnaire-9 (PHQ-9), respectively, wherein suicidal ideation and sleep-related problems were measured with PHQ-9 and Insomnia Severity Index (ISI). Results A total of 208 participants who completed one questionnaire were considered as valid. It was found that female respondents generally exhibited significantly higher levels of PSS-10, PHQ-9, and GAD-7 scores and shorter physical activity hours than male students. Students from rural areas demonstrated significantly higher levels of PHQ-9, suicidal ideation, and less portion of good or fair family economic support. Additionally, individuals from only-child families reported increased levels of activity hours (1.78 ± 2.07, p = 0.045) and a higher portion (55.10%, p = 0.007) of having clear future plan as compared with multiple-child families. The risk factors for anxiety symptoms (GAD-7 score) were higher scores of PSS-10 (OR = 1.15, 95% CI = 1.09–1.22), PHQ-9 (OR = 1.35, 95% CI = 1.22–1.49), and ISI-7 (OR = 1.14, 95% CI = 1.06–1.23), while owning a clear graduation plan was the protective factor (OR = 0.55, 95% CI = 0.31–0.98). Moreover, the risk factors for depressive symptoms (PHQ-9) included PSS-10 (OR = 1.10, 95% CI = 1.04–1.16), GAD-7 (OR = 1.38, 95% CI = 1.25–1.52), suicidal ideation (OR = 5.66, 95% CI = 3.37–9.51), and ISI-7 (OR = 1.17, 95% CI = 1.09–1.25). Approximately 98.08% of Chinese postgraduates studying stomatology reported experiencing at least moderate stress after the COVID-19 restrictions. Conclusion Within the limitations of this study, senior students were more inclined to stress, while anxiety symptoms were related to severer levels of stress, depression, and insomnia. Depressive symptoms were associated with higher levels of stress, anxiety, insomnia, suicidal ideation, and lower levels of self-reported well-being. Thus, psychological interventions for postgraduates should be timely and appropriately implemented by strengthening well-being, reasonably planning for the future, and good physique, thereby mitigating the psychological issues after COVID-19 restrictions.